The Effect of Green Human Resource Management and Green Transformational Leadership on Environmental Performance Mediated by Green Innovation Among Employees of Renewable Energy Companies in the Greater Jakarta Area - Satria Rizki Aviory; Fabian Emir Fazly; Tiara Puspa (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Businesses today are no longer solely profit-oriented; they are also expected to emphasize environmental sustainability. Therefore, environmental performance has become an important aspect for companies to consider. This study aims to analyze the influence of Green Human Resource Management (GHRM) and Green Transformational Leadership (GTLS) on Environmental Performance (ENVP), mediated by Green Innovation (GRIV), in companies operating within the renewable energy sector. This research employed a quantitative approach using purposive sampling techniques targeting employees of renewable energy companies in Jakarta. The object of this study consisted of employees working in renewable energy companies in the Greater Jakarta area, with a total sample of 276 respondents. Data analysis was conducted using the Structural Equation Modeling (SEM) method. The findings indicate that the majority of respondents worked in the electric vehicle (EV) transportation and automotive industry at the entry-level management position, were predominantly male, and had 1–5 years of work experience. The hypothesis testing results revealed that the supported hypotheses were the influence of GHRM on ENVP and the influence of GHRM on GRIV. Meanwhile, the unsupported hypotheses included the influence of GTLS on ENVP, the influence of GRIV on ENVP, the influence of GTLS on GRIV, the influence of GHRM on ENVP through GRIV as a mediator, and the influence of GTLS on ENVP through GRIV as a mediator.